Estudo dos parâmetros de soldagem em um revestimento de aço martensítico 410 nimo pelo processo fcaw pulsado utilizando modelos de regressão - Guimaraes, Jessika Batista (2020)
The present dissertation aims to analyze and optimize the welding parameters of the pulsed tubular wire (FCAW - Flux Cored Arc Welding) process by using martensitic stainless steel 410 NiMo as the filler metal and based on the geometry of the weld beads resulting from each test. The influence variables adopted were the average current, the pulsation frequency, the welding speed and the contact-tip-workpiece distance, each variable being tested at three different levels. The geometric characteristics evaluated, that is, the response variables, are the width, the reinforcement, the penetration, the reinforcement area, the penetration area, the convexity index and the dilution. In order to achieve the proposed objective, statistical techniques were used as analysis tools, and, in the first phase, the robust design method (Taguchi) was used to establish which combinations of parameters would be performed in each test, providing us with an L9 matrix. In a second phase, multiple linear regression models were built to select the most significant parameters, followed by multiple linear regression analyzes, that provided a model for optimization of parameters according to the set of responses. Based on the results generated, it was noticed that the average current affected almost all responses, with the exception of the reinforcement area. The welding speed just did not interfere with the penetration and in the penetration area. However, the contact-tipworkpiece distance significantly influences the reinforcement and the convexity index. Therefore it is sure, according to the tests done, that the biggest obtained width (11,51 mm) was at the medium current of 230 A, welding speed of 300 mm/min, pulsation frequency of 22.22 Hz and contact-tip-workpiece distance of 36 mm.